The Effectiveness of Economic Growth on Regional Expenditure in Central Java Province - Maulida Dewi Pangestika; Jeane Fransina Diana Talakua; Retno Febriyastuti Widyawati; Reni Eka Septiani (Efficient: Indonesian Journal of Development Economics, 2025)
Regional spending plays a strategic role in supporting economic development. This study analyzes the factors influencing regional spending in regencies and cities in Central Java Province using panel regression with five variables: effectiveness ratio, population, government assistance, HDI, and economic growth. Data from 2015-2022 were sourced from BPS and The Ministry of Finance. Spatial data were visualized using GIS-based mapping to illustrate fiscal self-sufficiency across regions. The results show that population size, HDI, and government assistance significantly affect regional spending. While the effectiveness ratio and economic growth are not significant. Spatial reveal that cities such as Semarang, Magelang, and Surakarta demonstrate higher fiscal independence, while regencies like Brebes remain highly dependent on central transfers. These findings suggest that improving human development and increasing local revenue capacity, especially in less developed regencies, are key strategies to enhance fiscal independence and promote regional economic resilience.